Pengembangan Media Ajar Flash Card Berbantuan Qr Code pada Materi Sistem Pencernaan untuk Meningkatkan Hasil Belajar Siswa Kelas XI - Pramudia Windi Indras Wari; Reny Dwi Riastuti; Sepriyaningsih Sepriyaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop valid, practical, and effective flashcard-based teaching media for the digestive system to improve learning outcomes for eleventh-grade students at SMA Negeri 2 Lubuklinggau. This research employed a Research and Development (R&D) method using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation. The results showed that the developed flashcard-based teaching media was categorized as very feasible by media validators, material validators, and language validators. Practicality tests based on teacher and student questionnaire responses indicated that the media was categorized as very practical for use in learning. Furthermore, effectiveness tests demonstrated improved student learning outcomes, as evidenced by increases in pre-test and post-test scores, with an N-Gain score of 0.79, which is considered high. In conclusion, the QR Code-based flashcard-based teaching media for eleventh-grade students at SMA Negeri 2 Lubuklinggau is valid, practical, and effective, making it suitable for use in biology learning. Keywords: ADDIE, Flash Card, QR Code, Digestive System and Learning Outcomes.